Analysis Of The Effect Of Net Profit, Operational Cash Flow, Free Cash Flow, Previous Year Cash Dividends On Cash Dividends In The Indonesia Stock - Fatia Fatimah; Sifriyani; Deni sunaryo; Etty Puji lestari (International Journal of Science, Technology & Management, 2022)
This study aims to determine the analysis of the effect of net income, operating cash flow, free cash flow, cash dividends in the previous year, on cash dividends. This study uses a food and beverage sub-sector research design. The research population amounted to 18 companies for 5 years from 2014-2018 and were picked up by 7 companies in a row to publish their financial statements. The method used in this data analysis using multiple linear regression analysis. Based on the results of the study, it can be concluded that: net income has no effect on cash dividends, operating cash flow has no effect on cash dividends, free cash flow has no effect on cash dividends, previous year's cash dividends have an effect on cash dividends.recommendations The company should pay attention to the cash dividend payments in previous years as an independent variable that affects the current year's cash dividend. Because the company will be attractive to shareholders whose preferences are related to dividend payout and stability. Investors want a stable dividend as a source of income embedded in shares that are paid the same amount of dividends every period. For further researchers, it is better to add the number of samples in the observation period of 6 years or 7 years, adding other variables such as Analyzing the relationship between Net profit, Operating Cash Flow with cash dividends, or Effect of accounting profit, cash profit, Free Cash Flow, Operating Cash Flow, leverage and current ratio to cash dividend. and can expand the research sample, not only to manufacturing companies but to more than one type of company.